Learning quality of students in a Medical school during the COVID-19 pandemic (Research, Society and Development, 2023)
Introduction: The education of healthcare students during social isolation was filled with various forms of adaptations and innovations. However, the outcomes of years of remote study are still being observed as the population returns to collective activities, needing studies to evaluate this matter. Objective: To evaluate the performance and challenges faced in the academic field during the COVID-19 pandemic at a Medical School in the Southern of Minas Gerais. Methods: A cross-sectional study using a pre-designed questionnaire distributed at a Medical School in the Southern of Minas Gerais. Results: 51% of students disagreed that online classes were as effective, in terms of knowledge, as in-person classes; 66.7% claimed that their level of concentration and study performance was not the same during social isolation; 54.9% of students feel insecure about the content learned during the COVID-19 pandemic; 54.9% reported difficulties in engaging in extracurricular activities during the pandemic period. Conclusion: It is noticed that the tools provided by the institution were useful and appeared to meet the demand. However, when it comes to the quality of learning, it does not seem to have improved, as more than half of the research participants feel insecure about the remotely delivered content during the pandemic.